Ribonuclease P - Liu, Fenyong; Altman, Sidney; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
Ribonuclease P (RNaseP), a ribonucleoprotein, is an essential tRNA processing enzyme found in all living organisms. Since its discovery almost 40 years ago, research on RNase P has led to the discovery of the catalytic properties of RNA, and of the only known, naturally occurring RNA enzymes, RNase P catalytic RNA. The description of the catalytic properties of RNA has provided fundamental insight into the RNA world and these catalytic properties are being harnessed as therapeutic and prevention strategies for acquired and inherited diseases. Ribonuclease P is the first book to provide a comprehensive collection covering all aspects of current research on RNase P. The topics include kinetic and structural analysis, mechanism of catalysis, and its regulation and biogenesis in prokaryotes, eukaryotes, and organelles. Furthermore, research progresses on developing RNase P as a potential drug target for antimicrobial development and as a gene-targeting tool for anti-infective and anticancer therapy are also included. This book should be of general interests to molecular biologists and biochemists in both the academic section and pharmaceutical industry.
History of RNase P and Overview of Its Catalytic Activity -- The Evolution of RNase P and Its RNA -- Over a Decade of Bacterial Ribonuclease P Modeling -- Structural Studies of Ribonuclease P -- Folding of Bacterial RNase P RNA -- Kinetic Mechanism of Bacterial RNase P -- Roles of Metal Ions in RNase P Catalysis -- Challenges in RNase P Substrate Recognition: Considering the Biological Context -- Archaeal RNase P: A Mosaic of Its Bacterial and Eukaryal Relatives -- Eukaryote RNase P and RNase MRP -- RNase P from Organelles -- Human RNase P and Transcription -- RNase P as a Drug Target -- Ribonuclease P as a Tool.
Keywords: Life sciences; Proteomics; Life Sciences; Proteomics